An Anti‐CD154 Domain Antibody Prolongs Graft Survival and Induces Foxp3+ iTreg in the Absence and Presence of CTLA‐4 Ig. Issue 11 (5th September 2013) - Pinelli, D. F.; Wagener, M. E.; Liu, D.; Yamniuk, A.; Tamura, J.; Grant, S.; Larsen, C. P.; Suri, A.; Nadler, S. G.; Ford, M. L.
Abstract: The use of monoclonal antibodies targeting the CD154 molecule remains one of the most effective means of promoting graft tolerance in animal models, but thromboembolic complications during early clinical trials have precluded their use in humans. Furthermore, the role of Fc‐mediated deletion of CD154‐expressing cells in the observed efficacy of these reagents remains controversial. Therefore, determining the requirements for anti‐CD154‐induced tolerance will instruct the development of safer but equally efficacious treatments. To investigate the mechanisms of action of anti‐CD154 therapy, two alternative means of targeting the CD40–CD154 pathway were used: a nonagonistic anti‐CD40 antibody and an Fc‐silent anti‐CD154 domain antibody. We compared these therapies to an Fc‐intact anti‐CD154 antibody in both a fully allogeneic model and a surrogate minor antigen model in which the fate of alloreactive cells could be tracked. Results indicated that anti‐CD40 mAbs as well as Fc‐silent anti‐CD154 domain antibodies were equivalent to Fc‐intact anti‐CD154 mAbs in their ability to inhibit alloreactive T cell expansion, attenuate cytokine production of antigen‐specific T cells and promote the conversion of Foxp3 + iTreg. Importantly, iTreg conversion observed with Fc‐silent anti‐CD154 domain antibodies was preserved in the presence of CTLA4‐Ig, suggesting that this therapy is a promising candidate for translation to clinical use. Abstract : Using a murine model of skin transplantation, this study demonstrates that treatment with a clinically translatable Fc–silent CD154–specific domain antibody attenuates alloreactive responses and leads to the conversion of Foxp3+ regulatory T cells, even in the presence of CTLA4–Ig.